Hybrid Governance Across National Jurisdictions as a Challenge to Constitutional Law - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
A technology often reaches perfection when its successor is already in place. Miraculously speedy and reliable punch card readers were finally available on the market when demand shifted to personal computers, to cite only one example. Do constitutions follow the same evolutionary pattern? Constitutional law, in general, and the doctrine of fundamental freedoms, in particular, are in admirable shape. Their dogmatics have been amply tested; they are elegant and rich. But they have been developed for the nation state. Yet governance reality is increasingly different. The state is competing with foreign, international and private governing authorities, or it is joining them in hybrid efforts. Will de-constitutionalization ensue? Or will the existing constitutions be able to face, or even alter, the new reality? This is a paper about governance. Hardly a term is more disputed in the social sciences. This paper looks at (potentially) global, not national or European governance. It therefore cannot avoid using the broadest of all possible definitions of governance. Since on the global scale there is no such thing as a widely undisputed higher order system, the term governance must comprise all modes of social ordering, by whatever actor or actor configuration. The focus of this paper is on divergent governance bodies, not governance tools. It does not want to explore whether the pertinent body uses (quasi-)legal rules, incentives, moral suasion or any other tool for governing the behavior of its addressees. It simply looks at who purports to change the behavior of a class of addressees, in the alleged interest of some protectees. Moreover, when it speaks of governance, the paper exclusively looks at intentional attempts to change the behavior of addressees.
Keywords: 340